Role of phagocyte extracellular traps during Mycobacterium tuberculosis infections and tuberculosis disease processes - García-Bengoa, María; Meurer, Marita; Goethe, Ralph; Singh, Mahavir; Reljic, Rajko; von Köckritz-Blickwede, Maren (Frontiers in Microbiology, 2023)
Mycobacterium tuberculosis (M.tb) infections remain one of the most significant causes of mortality worldwide. The current situation shows an emergence of new antibiotic-resistant strains making it difficult to control the tuberculosis (TB) disease. A large part of its success as a pathogen is due to its ability to persist for years or even decades without causing evident clinical manifestations. M.tb is highly successful in evading the host-defense by manipulating host-signaling pathways. Although macrophages are generally viewed as the key cell type involved in harboring M.tb, growing evidence shows that neutrophils also play a fundamental role. Both cells are known to act in multiple ways when encountering an invading pathogen, including phagocytosis, release of cytokines and chemokines, and oxidative burst. In addition, the formation of neutrophil extracellular traps (NETs) and macrophage extracellular traps (METs) has been described to contribute to M.tb infections. NETs/METs are extracellular DNA fibers with associated granule components, which are released upon activation of the cells by the pathogen or by pro-inflammatory mediators. On one hand, they can lead to a protective immune response by entrapment and killing of pathogens. However, on the other hand, they can also play a severe pathological role by inducing tissue damage. Extracellular traps (ETs) produced in the pulmonary alveoli can expand easily and expose tissue-damaging factors with Running Title 2 This is a provisional file, not the final typeset article detrimental effects. Since host-directed therapies offer a complementary strategy in tuberculosis, the knowledge of NET/MET formation is important for understanding potential protective versus detrimental pathways during innate immune signaling in TB. In this review, we summarize the progress made in understanding the role of NETs/METs in the pathogenesis of TB.